2015
DOI: 10.1007/s10877-015-9777-5
|View full text |Cite
|
Sign up to set email alerts
|

Wireless non-invasive continuous respiratory monitoring with FMCW radar: a clinical validation study

Abstract: Altered respiratory rate is one of the first symptoms of medical conditions that require timely intervention, e.g., sepsis or opioid-induced respiratory depression. To facilitate continuous respiratory rate monitoring on general hospital wards a contactless, non-invasive, prototype monitor was developed using frequency modulated continuous wave radar. We aimed to study whether radar can reliably measure respiratory rate in postoperative patients. In a diagnostic cross-sectional study patients were monitored wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…The ANOVA results showed that IJP sensor had high accuracy, good repeatability, and stability at different body postures. With no observable deviation from the reference sensor at all body postures, the accuracy of the IJP sensor was better than many sensors reported in the literature where the RR measured by stretchable sensor deviated from the reference value from 1.7% to more than 6% in different postures [4,12,[26][27][28][29][30].…”
Section: Ijp Sensor Accuracy: Comparison With Other Sensorsmentioning
confidence: 68%
“…The ANOVA results showed that IJP sensor had high accuracy, good repeatability, and stability at different body postures. With no observable deviation from the reference sensor at all body postures, the accuracy of the IJP sensor was better than many sensors reported in the literature where the RR measured by stretchable sensor deviated from the reference value from 1.7% to more than 6% in different postures [4,12,[26][27][28][29][30].…”
Section: Ijp Sensor Accuracy: Comparison With Other Sensorsmentioning
confidence: 68%
“… 11 16 Recently a new noninvasive technique was published that uses a radar system mounted above the patient’s bed to measure RR. 17 In this study, we used the RespiR8, a small and mobile device that relies on the detection of humidity in the exhaled air (see Niesters et al 9 for a detailed description of the RespiR8 measurement technique). The current study, as well as our previous validation study, shows that the device allows long-term reliable assessment of RR.…”
Section: Discussionmentioning
confidence: 99%
“…These two signals are then multiplied with the low pass filter output as expressed (4) and the results are written as (5) and (6). After the high-frequency component is removed by using LPF then the LPF output of the In-phase and Quadrature branch is used to obtain the phase data by calculating the inverse tangent as determined using (7). Theoretical analysis of IQ demodulation technique implementation for processing the FMCW output that is described in this section shows that the proposed modifications in the post-processing on FMCW can be used to determine the small displacement that occurred to the target.…”
Section: IImentioning
confidence: 99%
“…The CW radar system was studied in [5] for detecting respiratory vital signs. However, the CW system is not able to detect the distance of the target or the position of a small shift so this will make it difficult to do multi-target detection.Meanwhile, FMCW radar was proposed in [6]- [7]. Compared with UWB and CW radars, FMCW radar has advantages such as better resolution range, simple transmitter architecture and its resistance to interception [6].…”
Section: Introductionmentioning
confidence: 99%